Pengaruh Gaya Mengajar Guru Terhadap Hasil Belajar Matematika Siswa - Rahmah , Hidayati; Pardi, Habib Husnial (Mathematic Education Departement, State Islamic University of Mataram, 2023)
Abstract This study aims to determine whether there is an influence of the teacher's teaching style on students' mathematics learning outcomes in the case study flat-sided geometric material at Pringgasela 1 Public Middle School. This research is a quasi-experimental or quasi-experimental quantitative research with a non-equivalent posttest-only control group design. The population in this study were students of class VIII SMPN 1 Pringgasela. In taking the sample, the researcher used a purposive sampling technique because the researcher took a sample of 2 classes whose population actually consisted of 7 classes with the consideration that the selected samples had the same abilities. The data in this study were taken using questionnaires and tests, questionnaires to see differences in teacher teaching styles, and tests to see the effect of teacher teaching styles on student mathematics learning outcomes. Based on the results of the questionnaire data, the average experimental class was 64.91 and the control class was 61.08. The results of the test data obtained an average of 71 experimental classes and 63,594 control classes. To find out that there is influence of the teacher's teaching style on students' mathematics learning outcomes, the researcher analyzed the data using the -test. Based on the results of data analysis in the questionnaire obtained tcount = 2.06 and ttable = 1.999 and for student learning outcomes data obtained tcount = 2.05 and ttable = 1.999. Obtained tcount > ttable at a significance level of 5%, it can be concluded that there is an influence of the teacher's teaching style on the mathematics learning outcomes of class VIII students of SMPN 1 Pringgasela